"It only takes two minutes to ask"—a qualitative study with women on using the FIGO Nutrition Checklist in pregnancy. (7th September 2020) - Killeen, Sarah Louise; Callaghan, Shauna L.; Jacob, Chandni Maria; Hanson, Mark A.; McAuliffe, Fionnuala M.
Abstract: Objective: To gain an in‐depth understanding of how the FIGO Nutrition Checklist could work in clinical practice, from the perspective of pregnant women. Methods: This qualitative study was part of a pilot study of the FIGO Nutrition Checklist in the antenatal department of a tertiary‐level university maternity hospital in Dublin, Ireland. Individual semistructured phone interviews were conducted with pregnant women who had completed the FIGO Nutrition Checklist as part of the pilot. Interviews were transcribed verbatim and analyzed using content analysis after manual coding of transcripts. Themes and subthemes are described. Results: Ten interviews were completed. Subthemes related to the FIGO Nutrition Checklist emerged including ease of use and comprehension. Participants discussed how the tool could add value to their appointment by supporting initiation of nutrition conversations and highlighting nutritional issues. The first trimester was identified as the highest priority for using the FIGO Nutrition Checklist. The convenience of having nutrition addressed as part of standard care, rather than a separate appointment, also emerged. Conclusion: Women in this study had a desire for nutrition and weight to be addressed by clinicians during routine antenatal appointments. The findings support using the FIGO Nutrition Checklist to address this. Abstract : Pregnant women want to discuss nutrition and weight with their doctors during routine care. The FIGO Nutrition Checklist is an acceptable tool to support this.